Reduced Duration of Postchikungunya Musculoskeletal Pain in Rheumatological Patients Treated with Biologicals - Carlos A. A. de Brito; Claudia D. L. Marques; Rafael F. O. França; Janaína R. Monteiro; Marina C. M. de Brito; Fabiana Lopes; Anton Lima; Gabriel L. Marques; Maria Luisa Valadares; Angela L. B. P. Duarte (Journal of Tropical Medicine)
Chikungunya fever (CHIK) has caused important epidemic outbreaks in the Americas, with musculoskeletal involvement being the main manifestation, causing chronic symptoms in half of the affected patients. This study was performed to evaluate the clinical course of the infection in 168 patients with autoimmune inflammatory disease using biological disease-modifying antirheumatic drugs (bDMARDs), comparing this group with 56 household controls. Anti-CHIKV IgG serology was positive in 42 (25%) of the patients in the bDMARD group and in 15 (27%) of the controls (p=0.79). Of those with positive serology, 32 (76%) and 14 (93%) were symptomatic among subjects in the bDMARD and control groups, respectively (p=0.87). Persistence of musculoskeletal symptoms for more than three months occurred in 64% of the patients in the control group and only in 28% in the bDMARD group (p=0.021), maintaining a statistically significant difference only for users of anti-TNF. This study found that patients affected by chikungunya fever using bDMARDs did not present severe forms or complications in the acute phase of the disease, and patients using anti-TNF biologicals had a lower frequency of chronic joint symptoms than the household controls. This favorable outcome may be related to the cytokine blockade, with a reduction in the inflammatory response and joint damage.